Knowledge, attitudes and practices regarding rabies and exposure to bats in two rural communities in Guatemala. (December 2015) - Moran, David; Juliao, Patricia; Alvarez, Danilo; Lindblade, Kim; Ellison, James; Gilbert, Amy; Petersen, Brett; Rupprecht, Charles; Recuenco, Sergio
Abstract Background Rabies is a fatal encephalitis caused by rabies virus, of the genusLyssavirus . The principal reservoir for rabies in Latin America is the common vampire bat(Desmodus rotundus), which feeds routinely on the blood of cattle, and when livestock are scarce, may prey on other mammals, including humans. Although rabies is endemic in common vampire bat populations in Guatemala, there is limited research on the extent of exposure to bats among human populations living near bat refuges. Results A random sample of 270 of 473 households (57%) in two communities located within 2 Km of a known bat roost was selected and one adult from each household was interviewed. Exposure to bats (bites, scratches or bare skin contact) was reported by 96 (6%) of the 1, 721 residents among the selected households. Of those exposed, 40% received rabies post-exposure prophylaxis. Four percent of household respondents reported that they would seek rabies post exposure prophylaxis if they were bitten by a bat. Conclusions These findings demonstrate that exposure to bats in communities near bat roosts is common but recognition of the potential for rabies transmission from bats is low. There is a need for educational outreach to raise awareness of bat-associated rabies, prevent exposures to bats and ensure appropriate health-seeking behaviours for bat-inflicted wounds, particularly among communities living near bat roosts in Guatemala.